2013
DOI: 10.5665/sleep.2366
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Precocious Puberty and Obesity in Childhood Narcolepsy with Cataplexy

Abstract: NC occurring during prepubertal age is frequently accompanied by precocious puberty and overweight/obesity, suggesting an extended hypothalamic dysfunction. The severity of these comorbidities and the potential related risks require a multidiagnostic approach and a tailored therapeutic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 43 publications
4
77
0
5
Order By: Relevance
“…It has been previously reported that obesity is very common in narcolepsy [4]. BMI increase was clear also in our study while the majority of the subjects still stayed within the normal range.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It has been previously reported that obesity is very common in narcolepsy [4]. BMI increase was clear also in our study while the majority of the subjects still stayed within the normal range.…”
Section: Discussionsupporting
confidence: 71%
“…The main symptoms of narcolepsy are excessive daytime sleepiness, disturbed nocturnal sleep, cataplexy, sleep paralyses, and hallucinations during sleep-wake transitions. Other common associated features are increased weight, precocious puberty, behavioral problems, and psychiatric comorbidity [4][5][6]. There is a great heterogeneity in symptoms as some subjects are severely affected and disabled, whereas others manage without medication.…”
Section: Introductionmentioning
confidence: 99%
“…OSA is a comorbidity that is related to increased weight and obesity, has a high prevalence in narcolepsy [106][107][108], and can lead to a lack of narcolepsy recognition [27,109]. Central sleep apnea and OSA syndromes should be excluded before prescribing sodium oxybate, and sleep apnea treated prior to initiating sodium oxybate therapy.…”
Section: Treatment-related Exacerbation Of Comorbiditiesmentioning
confidence: 97%
“…It should be noted that both these targets of pattern A autoantibodies (MCH and POMC neurons) are also involved in the regulation of food intake [20,21]. This is highly relevant in the context of narcolepsy, where a rapid increase in body weight often occurs [22], and could be associated with an increased risk of cardiovascular disease as well as a significantly impaired quality of life [23]. Thus, it could be hypothesized that patients with autoantibodies against MCH/POMC neurons would have a higher body mass index than those without such autoantibodies.…”
Section: Narcolepsy: Genetic and Immunohistochemical Studiesmentioning
confidence: 99%